EFEK FRAKSI ETIL ASETAT EKSTRAK ETANOL AKAR PASAK BUMI (Eurycoma longifolia, Jack) TERHADAP AKTIVITAS FAGOSITOSIS MAKROFAG SECARA IN VITRO - Arifah, Aminda Nur; Nurkhasanah, Nurkhasanah (Universitas Ahmad Dahlan, 2014)
Eurycoma longifolia has been used as a remedy for detoxification, aphrodisiaca, anticancer andimmunistimulant. The quassinoids of pasak bumi root extract, have antioxidant activity andimmunomodulatory activity by increasing IL-12. This study aims to determine the effect of the ethylacetate fraction of ethanolic extract of pasak bumi root on macrophages phagocytic activity in vitro.Macrophages were isolated from peritoneal fluid of male Balb/Cmice, and thenwere cultured for 24hours in 24 well plate. The ethyl actetate fraction ethanolic extract of pasak bumi root withconcentration of 10, 50, and 100 µg/ml, lipopolysaccharides and dimethyl sulfoxide were added, andincubated for 1.5 hours. The phagocytosis tests was carried out by adding latex with density5x104/well and incubated for 1.5 hours at incubator (5% CO2,37oC). Macrophage were then stained byGiemsa. The results showed that the percentage of active phagocytic cells treated with ethyl actetatefraction of ethanolic extract of pasak bumi root of 10, 50 and 100 µg/ml, lipopolysaccharides, anddimethyl sulfoxide were 95.4%, 90%, 85.4%, 83.4%, and 79% respectively. Phagocytic capacity attreatment levels of 10, 50, and 100 µg/ml, lipopolysaccharides,and dimethyl sulfoxide were 469; 439.8; 360.8; 204.6; and 147.6 respectively. The result showed thatreatment of ethyl acetate fractionof ethanolic extract of pasak bumi root can increase the phagocytic activity of macrophages in vitro.